Strong matrix moment problem of Hamburger - Simonov, K. K. (Methods of Functional Analysis and Topology, 2006)
In this paper we consider the strong matrix moment problem on the real line. We obtain a necessary and sufficient condition for uniqueness and find all the solutions for the completely indeterminate case. We use M.G. Krein’s theory of representations for Hermitian operators and technique of boundary triplets and the corresponding Weyl functions.